Nurturing Diverse Generations of the Medical Workforce for Success With Authenticity: An Association of Black Cardiologists' Roundtable. Issue 1 (5th January 2023) - Haynes, Norrisa A.; Johnson, Michelle; Lewsey, Sabra C.; Alexander, Kevin M.; Anstey, D. Edmund; Dillenburg, Tierra; Njoroge, Joyce N.; Gordon, Debra; Ofili, Elizabeth O.; Yancy, Clyde W.; Albert, Michelle A.
Abstract : The COVID-19 pandemic exposed the consequences of systemic racism in the United States with Black, Hispanic, and other racial and ethnic diverse populations dying at disproportionately higher rates than White Americans. Addressing the social and health disparities amplified by COVID-19 requires in part restructuring of the healthcare system, particularly the diversity of the healthcare workforce to better reflect that of the US population. In January 2021, the Association of Black Cardiologists hosted a virtual roundtable designed to discuss key issues pertaining to medical workforce diversity and to identify strategies aimed at improving racial and ethnic diversity in medical school, graduate medical education, faculty, and leadership positions. The Nurturing Diverse Generations of the Medical Workforce for Success with Authenticity roundtable brought together diverse stakeholders and champions of diversity and inclusion to discuss innovative ideas, solutions, and opportunities to address workforce diversification.